Perancangan Sistem Informasi Akademik Pertukaran Mahasiswa Merdeka Bagi Mahasiswa Inbound Universitas Pamulang Dengan Metode Personal Extreme Programming - Dedy Priyatna (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Student exchange will be a routine activity every month. The student exchange process which is carried out manually takes quite a long time due to the increasing number of students. In addition, mistakes and errors often occur. The purpose of this research is to build an application that can register student exchange quickly and accurately. Designing an application certainly requires a special method to help during the process. Based on the needs of the method development becomes one of the important elements in the development of information needs. The method used in designing this application is Extreme Programming which is a method that has four stages in its implementation, namely planning, designing, coding and testing. By going through these four stages, it is hoped that the results obtained will be maximized and can be more helpful in the required process. The results of this study are student exchange applications that can provide convenience in obtaining information quickly and accurately, and can reduce errors in the course calculation process.